A rare case of small cell neuroendocrine tumor of the urinary bladder - B Praveen; Jophy Varghese; H Krishnamoorthy; Biju S Pillai (Wolters Kluwer Medknow Publications, 2020)
Small cell neuroendocrine tumor of the bladder is a rare tumor characterized by poor differentiation and high aggressiveness. Very few cases worldwide have been reported till date. Recent literature shows equivalent survival data for localized disease treated with chemoradiotherapy combined with either bladder sparing surgery or radical cystectomy. We report a case of small cell neuroendocrine carcinoma of the bladder diagnosed after transurethral resection of bladder tumor, then followed by adjuvant chemotherapy for six cycles and awaiting radical cystectomy.